2016
DOI: 10.1103/physrevd.94.084014
|View full text |Cite
|
Sign up to set email alerts
|

Uninvited guest in mixed derivative Hořava gravity

Abstract: We revisit the mixed-derivative extension of Hořava gravity which was designed to address the naturalness problems of the standard theory in the presence of matter couplings. We consider the minimal theory with mixed-derivative terms that contain two spatial and two temporal derivatives. Including all terms compatible with the (modified) scaling rules and the foliation-preserving diffeomorphisms, we calculate the dispersion relations of propagating modes. We find that the theory contains four propagating degre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…In addition, Hořava gravity with mix spatial and time derivatives has been also studied recently in order to avoid unacceptable violations of Lorentz invariance in the matter sector [191,192]. Unfortunately, it was found that the theory contains four propagating degrees of freedom, as opposed to three in the standard Hořava gravity, and the new degree of freedom is another scalar graviton, which is unstable at low energies [193].…”
Section: With Non-projectability and U(1) Symmetrymentioning
confidence: 99%
“…In addition, Hořava gravity with mix spatial and time derivatives has been also studied recently in order to avoid unacceptable violations of Lorentz invariance in the matter sector [191,192]. Unfortunately, it was found that the theory contains four propagating degrees of freedom, as opposed to three in the standard Hořava gravity, and the new degree of freedom is another scalar graviton, which is unstable at low energies [193].…”
Section: With Non-projectability and U(1) Symmetrymentioning
confidence: 99%
“…Moreover, such a mechanism seems to be necessary to keep Lorentz violation at bay already for lower mass dimension operators in the standard model [43]. It has been suggested that the weak coupling between gravity and matter might suffice to suppress the percolation [44] but it is not clear how well this works in practice for Hořava gravity [45][46][47].…”
Section: Theoretical Considerations and Indirect Constraintsmentioning
confidence: 99%
“…Generically, the operators of the form (2.22) may compromise power counting renormalizability of the Hořava-Lifshitz gravity [64][65][66]. Therefore, they have been omitted in the original action (2.1).…”
Section: Jhep06(2016)020mentioning
confidence: 99%